Analisis Pengaruh E-Banking Dan Kualitas Pelayanan Terhadap Loyalitas Nasabah Di Bank Sumut Unit Usaha Syariah Dengan Komitmen Keagamaan Sebagai Variabel Moderating (Studi Kasus Bank Sumut Unit Usaha Syariah KCP Karya) - Khairani, Irna; Dalimunthe, Ahmad Amin; Lubis, Arnida Wahyuni (Jurnal Manajemen Akuntansi (JUMSI), 2024)
This study was conducted to examine the effect of e-Banking variables, and the quality of Service to customer loyalty with religious commitment as a moderating variable. This study used primary data sourced from customers at Bank Sumut Sharia Business Unit KCP Karya on January 17, 2022 to February 17, 2022. The population used in this study is the customer who came to the customer service and using sampling techniques purposive sampling, so obtained 58. Data processing is done with SPSS statistical program tools 26. The results showed that the data used in this study have met the data quality test, the test of classical assumptions, which include: no multicollinearity, no heteroscedasticity, and normally distributed data. From the results of regression analysis showed partially variable e-banking affect customer loyalty, and service quality affect customer loyalty.